2002
DOI: 10.1094/pdis.2002.86.10.1089
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Aggressiveness Among Isolates of Cercospora from Maize as a Potential Cause of Genotype-Environment Interaction in Gray Leaf Spot Trials

Abstract: The use of genetically resistant maize hybrids is the preferred means of control of gray leaf spot, caused by Cercospora zeae-maydis. One problem faced by maize breeders attempting to breed for resistance to gray leaf spot is the high degree of genotype-environment interactions observed in disease trials. In North Carolina gray leaf spot trials conducted at four locations in the western part of the state, we found consistent hybrid-location interactions over the 1995 and 1996 growing seasons. Isolates of C. ze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0
5

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 20 publications
1
26
0
5
Order By: Relevance
“…There was significant effect for genotype × location for grain yield. This finding was similar to findings of Carson et al (2002). The significantly different G × E interactions was recorded for grain yield in maize (Makumbi, 2005;Menkir & Ayodele, 2005).…”
Section: Resultssupporting
confidence: 88%
“…There was significant effect for genotype × location for grain yield. This finding was similar to findings of Carson et al (2002). The significantly different G × E interactions was recorded for grain yield in maize (Makumbi, 2005;Menkir & Ayodele, 2005).…”
Section: Resultssupporting
confidence: 88%
“…Carson et al (2002) and Brunelli et al (2008) previously observed that some isolates from the former group II, now C. zeina, did not produce Cercosporin.…”
Section: Introductionmentioning
confidence: 93%
“…Since most sources of resistance to C. zeae-maydis are considered to be quantitative, and no races of the pathogen are known at this time, the only difference among isolates is considered to be aggressiveness (Bair and Ayers, 1986;Dunkle and Carson, 1998;Carson et al, 2002). Based on current knowledge, it is likely that resistance to this pathogen will remain durable (Brown, 1995).…”
Section: Improving Host Resistancementioning
confidence: 99%